PENGARUH PEMENUHAN KEBUTUHAN BERPRESTASI TERHADAP SEMANGAT KERJA PARAMEDIS ( KASUS PERAWAT RUMAH SAKIT BINA KASIH PEKANBARU) - SUDADI, TAMBAH; ", Kasmirudin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study was conducted at Hospital Bina Kasih Pekanbaru is located on Jl . Saman Hudin No. 3-5 Pekanbaru Riau , which is a company engaged in medical services . The purpose of this study was to determine the effect of fulfilling the needs of the achievements of the hospital paramedics morale building pekanbaru love . The research methods include the location of the research conducted at the Hospital Bina Kasih Pekanbaru , types and sources of data used is primary data , where the data is obtained directly from the company , among others, the achievement of meeting the needs of the hospital paramedics performed bina love pekanbaru and secondary data annual data obtained from the company include data on the number of patients from the years 2008-2012 , and a general overview of the company , while the analysis of the data using descriptive statistical analysis method that uses a simple linear regelasi analysis , correlation test , test coefficient of determination .Based on the research that has been done can be obtained correlation r = 0.714 it is stated veriabel free and bound variables correlated Strong , after test results and the results of determination coefficient R Square of .510 . That is the fulfillment of a variable contribution of achievement by 51 % while the remaining 49 % is influenced by other variables not included in this study . And do t test results are t ( 7.286 ) > t table ( 2,008 ) dansig . ( 000 ) < 0.05 . This means meeting the needs of achievement variables were significant affects on morale paramedics .From the research, leaders should be cultivated Hospital Bina Kasih pekanbaru further enhance efforts to meet the needs of achievement paramedics, the paramedics achievement expectations need to rise and will be a positive influence and boost morale paramedic , so the paramedics have high perfomance .Keyword : need achievement, motivation , business competation.work Performance